34‐3: New Blue‐Phase Liquid Crystal Optimized for Color‐Sequential Displays. Issue 1 (May 2017) - Huang, Yuge; Chen, Haiwei; Tan, Guanjun; Tobata, Hitoshi; Yamamoto, Shin-ichi; Okabe, Eiji; Lan, Yi-Fen; Tsai, Cheng-Yeh; Wu, Shin-Tson
Abstract : An optimized blue‐phase liquid crystal (BPLC) with a moderate dielectric constant, manageable capacitor charging time, high voltage holding ratio, and submillisecond gray‐to‐gray response time at room temperature is developed. Using protruded triangular IPS electrodes, the operation voltage can be reduced to 15V while keeping 74% transmittance. Such a BPLC enables single‐TFT addressing and 240‐Hz operation. Potential application for color‐sequential displays is emphasized. Our new approaches have solved the most critical charging time issue and would accelerate the emergence of the long‐awaited blue‐phase LCDs. The primetime for BPLCD is around the corner.